Risk of Upper Gastrointestinal Bleeding in a Cohort of New Users of Low-Dose ASA for Secondary Prevention of Cardiovascular Outcomes - Cea Soriano, Lucía; García Rodríguez, Luis A. (Frontiers in Pharmacology, 2010)
The Health Improvement Network UK primary care database was used to identify a cohort of 38 077 individuals aged 50–84 years with a first prescription of low-dose acetylsalicylic acid (ASA; 75–300 mg/day) for secondary prevention of cardiovascular or cerebrovascular events during 2000–2007. From this cohort, 169 incident cases of upper gastrointestinal bleeding (UGIB) were identified. Controls with no UGIB (n = 2000) were frequency-matched to the cases by age, sex and follow-up time. A nested case–control analysis was performed to determine risk factors associated with UGIB. The incidence of UGIB was 1.1 per 1000 person-years (95% CI, 1.0–1.3). Low-dose ASA users with a history of peptic ulcer disease had an increased risk of UGIB compared with those without (rate ratio [RR], 4.59; 95% CI, 2.87–7.33). Concomitant use of ASA and clopidogrel (RR, 1.61; 95% CI, 0.85–3.05) or non-steroidal anti-inflammatory drugs (NSAIDs; RR, 2.92; 95% CI, 1.77–4.82) conferred an increased risk of UGIB compared with ASA monotherapy. Discontinuation of ASA therapy (RR: 0.71, 95% CI, 0.42–1.20) and PPI co-treatment given since the start of ASA therapy (RR, 0.56; 95% CI, 0.33–0.96) were associated with a reduced risk of UGIB. In conclusion, in a cohort of individuals receiving low-dose ASA for secondary prevention of cardiovascular or cerebrovascular events, patients with a history of peptic ulcer disease, or who were receiving clopidogrel or NSAIDs had an increased risk of UGIB. The prescription of PPI therapy at the initiation of low-dose ASA reduced the risk of UGIB by almost half.